Correlation between electrical resistivity and water content of soil - Lim, Chu Rui (2019)
The use of electrical resistivity of soil in geotechnical site exploration has gained popularity with the advancement of geophysical technology in recent years. It provides for a quicker and more economical approach in contrast with conventional methods such as borehole sampling. Its shortcomings include the interpretation of electrical resistivity data being less straightforward due to a myriad of factors surrounding the measurements of data. In this preliminary study, laboratory model tests have been carried out to investigate the correlation between the electrical resistivity of kaolin clay and two common geotechnical parameters: soil water content and salinity. Kaolin samples of water content between 40% to 80% at 3 different soil salinity were tested using the Wenner array configuration. Based on the fitting of experimental data, there is a good correlation between soil resistivity and water content. A piecewise function has been formulated where electrical resistivity of soil decreases exponentially with the increase in both soil water content and salinity. The study concludes with a site investigation and the recommendations for further work.